Penerapan eleman kemahiran generik dalam pengajaran guru PTV di Sekolah Menengah Pendidikan Khas Vokasional (SMPKV) di Malaysia - Adnan, Mohd. Fathi (2013)
This study was carried out to investigate the level of Generic Skills among Technical and Vocational Education (TVE) teachers in Secondary Schools Special Education Vocational (SMPKV) in Malaysia. There are three SMPKV operating in Malaysia in Shah Alam, Kulaijaya, and the latest in Kuantan. This study was conducted on 58 PTV teachers who teach in SMPKV using mixed methods research. Research instrument in the form of questionnaires and checklists set was used to collect data. Questionnaires were divided into two parts, Part A and Part B. Part A is related to the background while Part B based on the objectives of the study. Checklist set covers methods of teaching and methods of application are implemented. The raw data obtained were analyzed using the software "Statistical Packages for Social Science" (SPSS) version 17. Analysis of studies reported in the form of descriptive and inferential percentage, mean, rank, T-test and ANOVA test. The results showed that the level of generic skill elements of TVE teaching in SMPKV is high. In addition, the TVE teachers in SMPKV are frequently using the workshop to apply the elements of generic skills. Teaching methods which are used to apply the elements of generic skills are discussions, the project method and lecture method. The study proves that there is no significant difference on the level of implementation and application of methods based on various elements of the generic skills of demographic factors. Discussion focused on the problems and recommendations to the stakeholders were made to improve the implementation of elements of generic skills in teaching TVE in SMPKV in Malaysia.